Integrated advertising in video game: Persuasive communication strategies and perception in Generation Z - Bonales-Daimiel, Gema; Gutiérrez-Manjón, Sergio (Street Art & Urban Creativity, 2026)
This study examines how Generation Z perceives advertising in Roblox and Fortnite, video games that integrate brands into immersive experiences. A longitudinal study was conducted between 2022 and 2025. The results indicate that advertising is viewed positively when it does not interfere with gameplay and is associated with emotions or cultural elements. Roblox stands out for its persistent brand universes and connection to physical products, while Fortnite excels in high-impact global collaborations. In both cases, the avatar functions as a symbolic identity. Nevertheless, risks such as social pressure, impulsive spending, and progressive monetisation emerge.